ANALISA PENGARUH PERTUMBUHAN KREDIT, JENIS KREDIT, TINGKAT BUNGA PINJAMAN BANK DAN INFLASI TERHADAP KREDIT BERMASALAH - Saputro, Arfan Rachmadias; Sarumpaet, Susi; Prasetyo, Tri Joko (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Abstract: This research was conducted to analyze the effect of loan growth, loan type, interest and inflation on non-performing loan. Samples were focused on Indonesian commercial banks. Multiple regression linear analysis was used, whereas the samples were obtained using purposive sampling method. Total sample consists of 82 commercial banks with financial statements for the year of 2013 to 2017. Result shows that each variable; loan growth, loan type and interest have a positive effect on non-performing loan. On the other hand, inflation has a negative effect. Keywords: Loan Growth, Loan Type, Interest, Inflation, Non-Performing Loan.